2021
DOI: 10.3390/su13158464
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Social Impacts of Curfew during the COVID-19 Outbreak in Kuwait: A Cross-Sectional Study

Abstract: The Coronavirus (COVID-19) pandemic in Kuwait led to a nationwide curfew between 22 March and August 2020. The purpose of this study was to evaluate the impact of the COVID-19 curfew during the pandemic on Kuwaiti citizens and residents. A cross-sectional survey was used to collect data from Kuwaiti residents over the age of 21 through an online questionnaire shared via social media, including WhatsApp and Facebook. Data collection occurred between 18 June and 15 July 2020. Data from 679 respondents (57.9% fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The rapidly spreading behavior of COVID-19 has drastically altered the daily lives of people globally [ 59 ]. As a result, unprecedented mental health concerns now exist worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The rapidly spreading behavior of COVID-19 has drastically altered the daily lives of people globally [ 59 ]. As a result, unprecedented mental health concerns now exist worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…The link of the semi-structured e-questionnaire, consisting of both open and closed-ended items, was shared on student community pages through social media such as Facebook, Messenger, and WhatsApp, and forwarded using other means including emails. Data were collected using the snowball sampling technique, where the participant was requested to forward the link of the e-questionnaire to other individuals in his/her social network 5 , 50 , 51 . The participants were invited to complete the survey voluntarily.…”
Section: Methodsmentioning
confidence: 99%
“…Kuwait COVID-19 survivors had lower working memory, monitoring, and inhibition than healthy controls (Alhuwailah & Shuwiekh, 2022). The few empirical studies that investigated the impact of COVID-19 in Kuwait found elevated levels of depression and anxiety (Alsairafi et al, 2021; Alsharji, 2020; Burhamah et al, 2020; Salman et al, 2021). There have been no other studies that have assessed the prevalence of PTSD, CPTSD, or executive dysfunction in the context of the COVID-19 outbreak in Kuwait.…”
Section: Hypothesesmentioning
confidence: 99%